2023
DOI: 10.3390/rs15235527
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Detection of Forest Fire Smoke in UAV Aerial Imagery Based on an Improved Yolov5 Model and Transfer Learning

Huanyu Yang,
Jun Wang,
Jiacun Wang

Abstract: Forest fires pose severe challenges to forest management because of their unpredictability, extensive harm, broad impact, and rescue complexities. Early smoke detection is pivotal for prompt intervention and damage mitigation. Combining deep learning techniques with UAV imagery holds potential in advancing forest fire smoke recognition. However, issues arise when using UAV-derived images, especially in detecting miniature smoke patches, complicating effective feature discernment. Common deep learning approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The latter is further subdivided into hierarchical or partitional methods, offering a variety of algorithms to choose from [ 24 , 45 , 46 , 47 ]. In this study, we employed the K-means algorithm, which falls under the category of partitional algorithms [ 47 , 48 ]. K-means clustering partitions the data into distinct clusters based on the similarity of data points, providing a straightforward and efficient approach to clustering analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is further subdivided into hierarchical or partitional methods, offering a variety of algorithms to choose from [ 24 , 45 , 46 , 47 ]. In this study, we employed the K-means algorithm, which falls under the category of partitional algorithms [ 47 , 48 ]. K-means clustering partitions the data into distinct clusters based on the similarity of data points, providing a straightforward and efficient approach to clustering analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, previous work has shown that K-means is accurate and computationally efficient compared to others [ 47 , 49 ]. Additionally, several authors have succeeded in combining K-means clustering with Deep Neural Networks [ 48 ], suggesting it is a suitable choice for our purposes of exploring feature distributions in the data.…”
Section: Methodsmentioning
confidence: 99%
“…The reason why grids can generate prediction boxes is simple. Each grid has several (usually three) template prediction boxes, each with pre-defined width, height, coordinates, and confidence [8] . Confidence represents the probability of the presence of an object within the grid.…”
Section: Summary Of Yolov5mentioning
confidence: 99%
“…Current models for forest-fire-image detection rely on generating anchors or proposals for detection [33]. In this article, an innovative detection model named FSNet is proposed for detecting fire spots and smoke in forest-fire images.…”
Section: Forest Fire and Smoke Detectionmentioning
confidence: 99%